2022
DOI: 10.3390/geosciences12020057
|View full text |Cite
|
Sign up to set email alerts
|

Vestiges of the Pre-Caledonian Passive Margin of Baltica in the Scandinavian Caledonides: Overview, Revisions and Control on the Structure of the Mountain Belt

Abstract: The Pre-Caledonian margin of Baltica has been outlined as a tapering wedge with increasing magmatism towards the ocean–continent transition. It is, however, well known that margins are complex, with different and diachronous evolution along and across strike. Baltica’s vestiges in the Scandes have complexities akin to modern margins. It included a microcontinent and magma-poor hyperextended and magma-rich segments. It was probably up to 1500 km wide before distal parts were affected by plate convergence. Chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 109 publications
(246 reference statements)
0
4
0
Order By: Relevance
“…Sketch map (top) and vertical W–E cross section (bottom), illustrating the inferred origin of the Kråkfjord protolith at an Ordovician slow‐spreading centre near continent Baltica (palaeogeography adapted from Andersen et al, 2022). The cross section outlines an extended transition zone between the continental shelf of Baltica in the east and the Iapetus Ocean in the west.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sketch map (top) and vertical W–E cross section (bottom), illustrating the inferred origin of the Kråkfjord protolith at an Ordovician slow‐spreading centre near continent Baltica (palaeogeography adapted from Andersen et al, 2022). The cross section outlines an extended transition zone between the continental shelf of Baltica in the east and the Iapetus Ocean in the west.…”
Section: Discussionmentioning
confidence: 99%
“…A third scenario for the origin of the Kråkfjord complex, which we favour, is an oceanic spreading ridge near to or within a Cambro-Ordovician hyper-extended OCT zone along southern Baltica (Figure 12). Andersen et al (2012Andersen et al ( , 2022 and Jakob et al (2017Jakob et al ( , 2019 propose that ribbons or microcontinents of Baltica crust were separated from the Baltica mainland by hundreds of kilometres of hyperextended crust during the Late Cambrian-Ordovician. The crystalline thrust sheets of the Middle Allochthon of southwestern Norway, for example, the Jotun and Lindås nappes, are thought to represent these ribbons or microcontinents.…”
Section: Scenario 3: An Oct Zone Along Southern Balticamentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Young (2018) suggested that the study area comprised delaminated parts of the upper Baltica crust. Moreover, based on U-Pb dating of intrusive rocks, Jakob et al (2017) and Andersen et al (2022) suggested that the Baltica margin experienced extension from the Late Cambrian until the Middle Ordovician. In such a context, lithospheric thinning (and related exhumation of the mantle) would have caused a temperature increase of the crust (including the mafic lenses), potentially up to 600 C. In this case, the stacking of the allochthons from the hyperextended margin would result in compression during the first stages of shortening, perhaps up to the inferred amphibolite facies pressure conditions.…”
Section: Geodynamic Implicationsmentioning
confidence: 99%